“Case report”: Whole-exome sequencing reveals compound heterozygous variants in the EIF2B5 gene in a familial case of vanishing white matter - Savy, Sofía; Montes, Francisco A.; Grosso, Carola L.; Laróvere, Laura E.; Silvera-Ruiz, Silene M.; Carro, Gerardo H.; Guelbert, Guillermo; Becerra, Adriana; Morales, David; Nicola, Juan P. (Frontiers in Genetics, 2025)
Vanishing white matter (VWM) is a rare autosomal recessive leukodystrophy associated with pathogenic variants in any of the five genes (EIF2B1-5) that encode subunits of the eukaryotic translation initiation factor 2B (eIF2B). Here, we present a case of a 26-year-old female patient from a non-consanguineous Amerindian Bolivian family, with clinical and neuroimaging findings suggestive of early-onset VWM, characterized by slowly progressive neurological deterioration in the absence of ovarian disorder. Whole-exome sequencing revealed a novel pair of compound heterozygous variants in the EIF2B5 gene, confirming the diagnosis of leukodystrophy with VWM and bringing closure to a nearly 20-year diagnostic odyssey. The identified c.318A>T (p.Leu106Phe) and c.1688G>A (p.Arg563Gln) in the EIF2B5 gene were classified as pathogenic and likely pathogenic, respectively, according to the American College of Medical Genetics and Genomics. Complementary Sanger sequencing revealed that the variants co-segregated with the phenotype in the pedigree, providing strong evidence of autosomal recessive inheritance of the disease, and enabling the molecular diagnosis of two asymptomatic sisters with white matter lesions on neuroimaging. This case underscores the heterogeneous nature of VWM, and emphasizes the relevance of integrating a comprehensive clinical evaluation, brain magnetic resonance imaging, and genetic studies in the diagnosis of leukodystrophies.